ORGANIZATIONAL CHANGE READINNES PADA UNIVERSITAS X - Azhar El Hami; Zahrotur Rusyda Hinduan (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2015)
This study was aimed to capture the readiness to change of the “X” University as an organization regarding to the vision is becoming a world class university. Using the organizational change readiness concept by Sutanto (2008) that covering 7 aspects namely perception toward change, vision of change, mutual trust and respect, change initiative, management support, acceptance, and organization manages the change process. Respondent was 121 employees of the University „X‟ from two faculties who met the criterion. This was a quantitative research that using survey method. The result has shown that two aspects namely vision of change and acceptance were important ones that have effect on organizational change readiness of the “X” university.